1988
DOI: 10.1103/physrevlett.60.995
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-beam neutron-lifetime measurement

Abstract: We have measured the neutron lifetime using a superconducting electron spectrometer and a pulsed beam of cold neutrons. Spatially defined neutron bunches are completely contained within the spectrometer's active volume while the /3-decay rate is measured. The flux is determined from the radioactivity of nearly totally absorbing thick samples of cobalt and gold exposed to the neutron beam. We obtain r" =876 ± 21 sec.PACS numbers: 13.30.Ce, 14.20.Dh, 23.40.Bw The measured neutron lifetime provides information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(11 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…[23]. We have tested the principle of n-decay from a propagating neutron cloud earlier with a free n-beam [26]. used, which at present is (99.770.1)% at 10% polarizer transmission [27] (relative to the incoming unpolarized n-flux).…”
Section: Continuous Vs Pulsed N-beammentioning
confidence: 99%
“…[23]. We have tested the principle of n-decay from a propagating neutron cloud earlier with a free n-beam [26]. used, which at present is (99.770.1)% at 10% polarizer transmission [27] (relative to the incoming unpolarized n-flux).…”
Section: Continuous Vs Pulsed N-beammentioning
confidence: 99%
“…[1][2][3] In the past decade, experiments have demonstrated several advantages of using ultra-cold neutrons for beta decay experiments. Measuring the decay of neutrons trapped in material bottles eliminates systematic errors associated with defining the volume and flux that have plagued neutron lifetime experiments with cold neutron beams [4][5][6][7] and therefore allows more precise measurements. [8][9][10][11][12][13] More recently, results obtained with the Los Alamos Neutron Science Center (LANSCE) UCN source 14,15 have demonstrated that the high polarizations and low backgrounds that can be obtained with spallation-driven, pulsed UCN sources can reduce the systematic errors in measuring the spin dependence of neutron beta decay 16,17 relative to cold neutron beam-based experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 and Table 1 summarize the present status of the heaviest elements known and their production and decay properties [20,21] 54 Cr, 58 Fe) and subsequent evaporation of 1-2 neutrons. The fragments decay within some 10~4-ls, mainly via the emission of 9-11 MeV ot-particles and (possibly) fission.…”
Section: A Very Long Lifetimesmentioning
confidence: 99%
“…In the experiment by Last et al [58], the neutrons in the pulse are counted by a cobalt beam stop, i.e. by activating a 59 Co sample and precisely measuring the decay γ-radiation.…”
Section: Precision Studies Of the Neutron Lifetimementioning
confidence: 99%